Supply response of West African agricultural households: implications of intrahousehold preference heterogeneity - Smith, Lisa C.; Chavas, Jean-Paul (International Food Policy Research Institute, 1999)
This paper explores the implications of preference heterogeneity between wives and husbands in nonresource-pooling rural West African households for the effect of crop price changes on agricultural production, i.e., their supply response. A semi-cooperative game-theoretic model of household decisionmaking, in which household members make unilateral time and income allocation decisions and negotiate over who controls these resources, is proposed. The model is used to show that Pareto efficiency in both production and consumption do not hold. It is then employed to simulate the supply response to cotton price increases accompanying agricultural sector liberalization in Burkina Faso in the early 1980s. The simulated semi-cooperative model predicts the cotton supply response of (monogamous) Burkinabé households to be 25 percent below that which would ensue in households facing the same production constraints yet whose members have identical preferences. The analysis indicates that in nonresource-pooling agricultural households, preference heterogeneity can be expected to mute supply response and may do so in a quantitatively significant manner. It illustrates how an intrahousehold approach that allows for such heterogeneity and for disaggregation of resource control by gender contributes to a better understanding of price effects.